Preliminary Antibacterial Activity of Eco-Enzymes Derived from Maluku Spice-Plant Residues Against Staphylococcus aureus and Escherichia coli - Jamilah; Dahlia Badui; Salma Samputri (Biosel Biology Science and Education, 2026)
Eco-enzymes derived from spice-plant residues may provide an environmentally friendly source of antibacterial compounds. This study evaluated eco-enzymes prepared from nutmeg fruit (BP), nutmeg leaves (DP), eucalyptus leaves (DK), and clove leaves (DC) using a 1:3:10 ratio of coconut sugar, plant residue, and water. Fermentation was conducted anaerobically for 90 days, and the products were screened against Staphylococcus aureus and Escherichia coli by disk diffusion at 10% concentration. Two commercial 70% alcohol antiseptics served as positive controls. After fermentation, all eco-enzymes were acidic with a final pH of approximately 4.8 and showed distinct sensory profiles. The clove-leaf eco-enzyme produced the largest mean inhibition zones against E. coli (14.22 ± 0.31 mm) and S. aureus (12.25 ± 0.41 mm). One-way ANOVA indicated that treatment significantly affected inhibition zones against E. coli (p < 0.001) and S. aureus (p < 0.001). HPLC screening suggested myristicin as dominant in BP, cineole in DK, and eugenol in DC. Overall, the results indicate preliminary antibacterial potential, especially for clove-leaf eco-enzyme, and support further studies using concentration gradients, MIC/MBC assays, and fully specified chromatographic methods. Keywords: Eco-Enzyme, Antibacterial Activity, Staphylococcus aureus, Escherichia coli, Clove Leaves.